Engineering Ultrathin MoS2 Nanosheets Anchored on N‐Doped Carbon Microspheres with Pseudocapacitive Properties for High‐Performance Lithium‐Ion Capacitors. Issue 7 (17th April 2019) - Jiang, Jiangmin; Zhang, Yadi; An, Yufeng; Wu, Langyuan; Zhu, Qi; Dou, Hui; Zhang, Xiaogang
Abstract: Lithium‐ion capacitors (LICs) are emerging as one of the most advanced energy storage devices by combining the virtues of both supercapacitor and lithium‐ion battery. The key point of constructing high‐performance LICs is to balance the electrochemical kinetics and capacity mismatch between battery‐type anode and capacitive‐type cathode materials. Herein, a strategy is presented for simultaneous manipulation of a MoS2 /N‐doped carbon microspheres anode and hierarchical porous carbon cathode by using polyimide precursor. Owing to the fast lithium diffusion rate, high pseudocapacitive behavior, and expanding the interlayer of the MoS2 composite network architecture, the material can achieve excellent rate capacity and cyclic stability. Hierarchical porous carbon has an ultrahigh specific surface area and superior capacitive behavior. A high‐performance LIC is successfully constructed by using the superior anode and cathode materials. The device can deliver a maximum energy density of 120 Wh kg −1 and keep the capacity retention of 85.5% after 4000 cycles, revealing the competition in advanced energy storage devices. Accordingly, the simultaneous manipulation of metal sulfide and hierarchical porous carbon by the same precursor can be used toward fabricating other ideal electrode structures for energy storage. Abstract : Lithium‐ion capacitors (LICs) are emerging as the most advanced energy storage devices. A strategy of using 3D MoS2 /N‐NPCM composite architecture as anode coupling with NPMC‐A carbon cathode is presented to construct high‐performance LICs, which has a maximum energy density of 120 Wh kg −1 and a capacity retention of 85.5% after 4000 cycles, thus showing a promising application potential.